Canadian consensus on TRK‐inhibitor therapy for NTRK fusion‐positive sarcoma. Issue 9 (4th August 2021) - Simmons, Christine; Deyell, Rebecca J.; MacNeill, Andrea J.; Vera‐Badillo, Francisco E.; Smrke, Alannah; Abdul Razak, Albiruni R.; Banerji, Shantanu; McLeod, Deanna; Noujaim, Jonathan
Abstract: Malignant sarcomas are rare accounting for <1% of all adult solid malignancies and approximately 11% to 13% of all pediatric malignancies. TRK‐inhibitors have demonstrated robust and long‐lasting responses in patients with NTRK fusion‐positive solid tumors, including sarcoma. Access to these agents in many jurisdictions such as Canada remains limited. We undertook a modified Delphi consensus to articulate and convey the clinical importance of these agents for the Canadian sarcoma community. A systematic search of published and presented literature was conducted to identify clinical trials reporting outcomes on the use of TRK‐inhibitors in relapsed/refractory NTRK fusion‐positive sarcoma. Three main consensus questions were identified: (a) is there currently an unmet clinical need for systemic therapy options in relapsed/refractory sarcoma? (b) do TRK‐inhibitors confer a clinical benefit to patients with NTRK fusion‐positive sarcoma? (c) do phase I/II basket trials provide sufficient evidence to justify funding of TRK‐inhibitors in NTRK fusion‐positive sarcoma? Response rates to the first and second surveys were 57% (n = 30) and 42% (n = 22), respectively. There was strong agreement among the Canadian sarcoma community that there was unmet clinical need for effective systemic therapy options in relapsed/refractory sarcoma, that TRK‐inhibitors are a safe and effective treatment option for patients with NTRK fusion‐positive sarcoma, and that available phase I/II basket trials provide sufficient evidence to support funding of these agents in relapsed/refractory NTRK fusion‐positive sarcoma. TRK‐inhibitors are a safe and effective systemic therapy option for patients with relapsed/refractory NTRK fusion‐positive sarcoma.